FRI0534 Physical Activity, Overweight, and Leisure Time Activity in a Cohort of Juvenile Idiopathic Arthritis Patients. (9th June 2015) - Sherman, G.; Moshe, V.; Haviv, R.; Reis, Y.; Consolaro, A.; Ruperto, N.; Uziel, Y.
Abstract : Background: Juvenile idiopathic arthritis (JIA) might lead to decreased physical activity and quality of life. Physical activity is an important part of children's social development and is important in the treatment of JIA. Objectives: To characterize clinical aspects, physical activity rates, obesity, and screen time in a group of JIA patients Methods: Over a 6-month period, a cohort of consecutive JIA patients in the Pediatric Rheumatology Clinic at Meir Medical Center were evaluated and compared to healthy children. Information on disease activity, type and amount of physical activity (using the Modified Godin Leisure-Time Exercise Questionnaire), and daily screen time hours were collected. Results: 97 patients and 98 matched controls completed the questionnaires. Among the patients, 56% had oligoarthritis, 22% polyarthritis and 17% systemic disease. Disease activity among all JIA sub-groups was low (average of 1.7 out of 10), two thirds of patients had a disease activity lower than 3, only 4% over 5, and 56% were in clinical remission. Obesity rates in the patient group and control groups were 21.5% and 19.4%, respectively. Physical activity levels were similar in both groups. There was a statistically significant reverse correlation between physical activity and age. The "total weekly leisure activity" of the control group was higher (46.9 vs. 38.4 hours, respectively). Daily screen time was similar (3.2 vs. 2.9 hours). Conclusions: Physical activity, screen time hours and obesity rates were similar between JIA patients and controls. This lack of difference could be attributed to the clinical remission following early, aggressive, treat-to-target therapy. Disclosure of Interest: None declared